SIMPLE VIRILIZING CONGENITAL ADRENAL HYPERPLASIA: Presentation in a Female Child with Genital Ambiguity undergoing Genitoplasty (A Case Report) - -, Nurhaen; Duarsa, G. W. K. (BALI MEDICAL JOURNAL; Volume 1, Number 3, September-December 2012, 2013)
Objective: our objective was to display the presentation of simple virilizing Congenital Adrenal Hyperplasia (CAH) with genital ambiguity and severe virilization of the external genitalia, influencing growth, height and weight, bone maturation, quality of life and hence undergoing genitoplasty. Surgical treatment was aimed to obtain a more natural psychological and sexual development and the type of surgical repair performed was tailored based on individual patient’s anatomy findings. Case : we report a case of a 3-year old female with simple virilizing CAH, diagnosed due to genital ambiguity, severe virilization, clitoromegaly, external genital pigmentation, precocious pubic hair, previously was under treatment with glucocorticoid replacement therapy for 2 years since newborn and neglected due to discontinuing the hormonal treatment for one year duration, underwent several clinical studies including chromosomal study for sex determining, pelvic ultrasonography for internal anatomical details and bone age study for skeletal maturation, given stress dose steroids pre-operatively and followed by genital reconstructive surgery (genitoplasty). A clitorectomy and labioplasty approach were performed. At time of surgery cystoscopy was carried out prior to the surgical repair. Results : Management of virilizing CAH child with ambiguous genitalia demands multidisciplinary and interdisciplinary approach. The team‘s major challenge is to use the feasible means to make the least bad choice in order to select a gender able to match the individual identity, social identity, and behavioral identity. Surgical option should be tailored, one stage surgery, at early age and performed according to the individual anatomy findings.
Keywords: congenital adrenal hyperplasia, simple virilizing, genital ambiguity, genitoplasty.